Quad trap: an alternative approach to increase trapping efficiency of the male bagworm, Metisa Plana Walker - Noorhazwani Kamarudin; Siti Nurulhidayah Ahmad; Mohd Najib Ahmad; Nur Robaatul Adhawiyah Mohd Ali Napiah; Shamsilawani Ahamed Bakeri; Mohamad Rosman Sulaiman; Mohamed Mazmira Mohd Masri; Mohd Fahmi Keni (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mass trapping plays an important role in insect pest management strategies by effectively monitoring and controlling the pest population. Various trap designs have been developed to optimise these traps' capture efficiency and reliability. This study compares two trap designs, the Mono trap and the Quad trap, for controlling the male of bagworm in oil palm plantations. The Mono trap is made from a one-unit white transparent plastic bag with two wooden poles, while the Quad trap is a four-unit white transparent plastic bag connected with raffia rope and tied between two oil palm trunks. There is a significant difference in the mean number of male moths captured between the two traps (P-value = 0.0028), where Quad trap captured more male moth (594.2) than Mono trap (68.4). The results show that the Quad trap is significantly more efficient in terms of male moth capture, increasing the number of male moths caught (m2) by 54% and reducing half installation time from 6 minutes to 3 minutes. The cost per unit trap is significantly cheaper at RM10.05 per set compared to the Mono trap (RM25.40). The Quad trap offers an alternative method of male moth control, making it easy to set up, affordable price, and requires no heavy lifting equipment. Thus, mass trapping of male moth bagworms using a Quad trap could complement other insect pest management components more effectively.